Strategi LSM Jemari Sakato Dalam Mendorong Partisipasi Masyarakat Terhadap Pembangunan Di Kota Padang - Muhammad Irfan; Rayhana Clarisa; Sabhena Binta Hadira; Yulia Hanoselina; Rahmadhona Fitri Helmi (CV. ITTC INDONESIA, 2025)
This study aims to examine the strategies implemented by the Non-Governmental Organization (NGO) JEMARI SAKATO in increasing active community participation in the development process in Padang City. Community participation is considered an important factor in realizing inclusive and sustainable development. By utilizing a qualitative approach and case study method, this study explores the various efforts and methods taken by JEMARI SAKATO in encouraging community participation in the planning, implementation, and monitoring stages of development programs. The results of the study revealed that JEMARI SAKATO implemented various strategies such as community assistance, public discussion forums, policy advocacy, and collaboration with various stakeholders. The effectiveness of these strategies was analyzed based on the level of community participation achieved, the perceived impact of the development program, and the challenges and opportunities faced by NGOs in their implementation. These findings are expected to enrich the understanding of the strategic role of NGOs in facilitating community participation in local development and provide practical recommendations for strengthening similar roles in other urban contexts.